Pelatihan Digital Marketing dan Pendampingan Legalitas Untuk Mengembangkan Usaha UMKM Entrepreneur Expo UNAIC - Yuwono, Tri; Tajudin, Tatang; Nur Triwibowo, Rony; Natasya Sefiani, Herlin; Anggaraksa, Wiman (Politeknik Negeri Cilacap, 2024)
UMKM is an economic sector that has an important role in national development. However, MSMEs still face various challenges, such as low mastery of digital marketing and business legality. Therefore, the purpose of this community service activity is to provide digital marketing training and legal assistance for MSME Entrepreneur Expo UNAIC. This community service uses a participatory method, where the service team works with participants in planning, implementing, and evaluating activities. The results of the community service show that the participants experienced an increase in knowledge, skills, and motivation in developing their business through digital marketing and business legality. Participants also received assistance and consultation from the service team in overcoming problems encountered in digital marketing and making legal business identification numbers and halal certificates. This community service activity provides benefits for participants, the service team, and the wider community. This activity also contributes to the development of science and technology in the field of digital marketing and business legality, especially halal certificates. This activity is expected to be an inspiration and model for other similar community service activities.